The Effect of The Proportion of Broccoli with Papaya, Pineaple, and Jackfruit on The Quality of Vegetable Leather - Bagus Ramadhani; Ida Agustini Saidi (jurnal makanan tropis dan teknologi agroindustri, 2021)
The aims of this research to determine effect the proportion of broccoli, papaya, pineapple, and jackfruit on vegetable leather quality. This research was conducted in laboratory of Muhammadiyah Sidoarjo University from February until April 2019 was used Randomized Block Design single factor was proportion of broccoli: papaya (25%:75%), (50%:50%), (75%:25%), broccoli: pineapple (25%:75%), (50%:50%), (75%:25%), broccoli: jackfruit (25%:75%), (50%:50%), (75%:25%). Data was analyzed using analysis of variance (Anova) followed by BNJ 5%. The result showed the proportion of broccoli with papaya, pineapple, and jackfruit was significant affected on fiber content, water content, ash content, pH, yield, and color of vegetable leather. The best treatment was the proportion of broccoli with jackfruit (25%:75%) had fiber content 2,15%, water content 19,38%, ash content 1,17%, pH 4,63, color L*a*b 46,82*-5,08*9,84, yield 55,16% and hedonic test of color 5,43, aroma 4,93, texture 4,97, and taste 5,07.